AB0372 PREGNANCY OUTCOME IN WOMEN WITH SJÖGREN SYNDROME IS OFTEN COMPLICATED BY PLACENTA INSUFFICIENCY. (2nd June 2020) - Troester, I.; Kollert, F.; Zbinden, A.; Raio, L.; Foerger, F.
Abstract : Background: Chronic inflammatory rheumatic diseases are often associated with a negative effect on pregnancy outcome. Most obstetrical complications are placenta-mediated such as preterm delivery and growths restrictions. In women with Sjögren syndrome, data on placenta- mediated complications are scarce and conflicting (1, 2). Objectives: To analyse neonatal outcome in women with Sjögren syndrome with focus on preterm delivery and growth restriction. Methods: We retrospectively analysed 23 pregnancies of 16 patients with Sjögren syndrome that were followed at our centre with regard to pregnancy outcome, medication and disease characteristics. Small for gestational age was defined as birthweight percentile <10 th . Preterm delivery was defined as delivery before 37, early term as delivery between 37-39 and term as delivery between 39-42 weeks of gestation. Results: Of 23 pregnancies, one ended in a miscarriage and 22 resulted in live births including one set of twins. Treatment used during pregnancy was hydroxychloroquine (20 pregnancies), prednisone (8), azathioprine (5) and cyclosporine (2). Concomitant treatment with low-dose aspirin was used in 9 pregnancies. Of the 22 live births, 17 were born at early term and 5 at term. There were no preterm deliveries. Median birth weight was 2820g (range 2095-3845g). Nine newborns (40.9%) were small for gestational age (SGA). Maternal treatment during these pregnancies was hydroxychloroquine in all cases and additional low-dose aspirin in three cases. Elevated CRP levels during pregnancy were found in 57% of the cases with SGA outcome. Only one woman with an SGA infant had positive anti-phospholipid antibodies. Regarding delivery mode, most patients had caesarean sections. Conclusion: In our cohort of women with Sjögren syndrome the prevalence of small for gestational age infants was high despite maternal treatment with hydroxychloroquine. Inflammatory markers could help to identify the patients at risk for placental insufficiency, yet prospective studies of larger cohorts are needed. References: [1]Gupta S et al; Sjögren Syndrome and Pregnancy: A literature review. Perm J 2017; 21:16-047 [2]De Carolis S et al; The impact of primary Sjögren's syndrome on pregnancy outcome: Our series and review of the literature. Autoimmun Rev 2014; 13(2):103-7 Disclosure of Interests: Isabella Troester: None declared, Florian Kollert Employee of: Novartis, Astrid Zbinden: None declared, Luigi Raio: None declared, Frauke Foerger Grant/research support from: unrestricted grant from UCB, Consultant of: UCB, GSK, Roche, Speakers bureau: UCB, GSK